Kepastian Hukum Kepemilikan Hak Atas Tanah Pasca Perjanjian Pinjam Nama (Nominee Arrangement) Dianggap Batal Demi Hukum - Febrina, Dwi Tiara; Sudiro, Amad (UNES Law Review, 2024)
Due to the fast-paced population increase, land, a valuable natural resource, is becoming more and more scarce. A societal crisis could be sparked by land, which is equally susceptible. Consequently, it is critical that the State equitably regulates land ownership. The right to utilize and profit from land is granted to the possessor. Land might have primary or secondary rights, depends on the terms of the agreement between the landowner and the potential secondary right holder. Land rights are transferred through buy and sale agreements. The acquisition of land rights is governed by national land law, which places limitations on foreign nationals. Their ownership rights are not granted; only the right to use the land is. Nominee agreements with Indonesian citizens are used by some foreign nationals to own. To stop foreigners from gaining control, the Indonesian government gives priority to land owned by Indonesian nationals. Criminals also conceal assets through the employment of nominees. Therefore, Indonesian law forbids foreign nationals from owning land. Under the guise of Indonesian citizens, foreign nationals can lawfully smuggle land into Indonesia through nominee arrangements. An agreement between a foreign national and an Indonesian national is involved in this.